CHARACTERISTICS OF INVESTMENT IN THE INNOVATIVE DEVELOPMENT OF AGRICULTURAL ENTERPRISES IN CONDITIONS OF UNCERTAINTY - Knysh, Serhii (Social Development: Economic and Legal Issues, 2026)
This article identifies the characteristics of investing in the innovative development of agricultural enterprises under conditions of uncertainty, highlights the associated challenges, and puts forward proposals regarding potential sources and avenues for growth and improvement. It has been established that the substantive essence of such investment involves the allocation of one’s own or borrowed funds to the latest developments in agricultural production to comprehensively improve it and increase profitability in the immediate and longer term. It has been established that, in conditions of uncertainty due to the enormous losses of the war, all entities in the agricultural sector face a shortage of their own financial resources for investment due to the destruction and reduction of operations, the loss of property complexes, and the reduction of labor resources. On the other hand, Russia’s invasion significantly increases investment risks. However, there is no alternative to the implementation of innovations to ensure the efficiency and competitiveness of agricultural enterprises, given the opportunities of the digital economy and its global spread. It has been determined that in Ukraine, investment in innovative development is being carried out based on high-tech frameworks for agricultural enterprises. This ensures the country’s positioning as a global food producer. Medium-sized and, in particular, small agricultural enterprises have significantly fewer investment opportunities. Furthermore, for them, innovative development may still entail the introduction of new material and technical resources or their modernization, i.e., the third technological paradigm. Therefore, investment in their innovations based on high-tech paradigms is of great importance. To address investment challenges, it is first and foremost necessary to take into account security factors in countering other threats, including the demining of the territory. This significantly alters the direction of innovation and investment, diverting them from core priorities, and affects the production costs and prices of food products. However, investment in the innovative development of agricultural enterprises, as a vital component of food and national security, must continue on the basis of improving the use of their own resources, state and international support, digital tools, and the latest forms and mechanisms.